Antecedents of the university students' intention to practise e-waste recycling / Nursyafiqah Najeehah Abdullah Rizzal ... [et al.] - Abdullah Rizzal, Nursyafiqah Najeehah; Kassim, Nurul Athirah; Rabun, Mohd Nazir (2021)
Electronic waste or simply known as e-waste has been a global crisis even before the Coronavirus disease (COVID-19) hit, and the number of e-waste have been rising sharply due to the outbreak. This is due to the fact that, during the pandemic, most of the education systems worldwide have switched to a new method of fully online learning. Therefore, every student needs to utilize the electronic devices and gadget to engage with the new method of learning. Hence, the amount of e-waste generated will be rising more rapidly than usual as there is massive usage of the gadgets and electronic devices during the pandemic. The e-waste disposal management in other countries is varied whereby it is properly recycled or improperly disposed. For example, some of the countries are exporting or dumping their e-waste to other countries such as in Nigeria and Ghana, Africa in which about 4 Million tons of waste are dumped illegally in landfills (Sivaraman, 2013) Moreover, Guiyu City in China, India and Philippines are also practising improper e-waste disposal by burning them. Moreover, some studies also pointed that, in the United States only some ewastes were recycled properly, and the rest were shipped to Hong Kong, Latin America and the Caribbean (Vidal, 2013). Other studies also found that there is still a high quantity of e-waste managed under improper methods by informal collectors in several nations, especially in Asia and Africa, such as China, Bangladesh, India, Thailand, Vietnam, Nigeria, and Ghana (Shamim, 2015).